Penerimaan Diri Korban Toxic Relationship dalam Menumbuhkan Kesehatan Mental - Ulin Nihayah; Ade Vinna Pandu Winata; Titin Yulianti (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2021)
Toxic relationship is one example of how then a problem that affects a person's relationship with his partner. This is usually indicated by a sense of competition from within the individual and the absence of cohesiveness. The purpose of this paper is to provide a better understanding of the self-acceptance of toxic victim relationships in fostering mental health, the author is also associated with a toxic victim case study entitled